2014
DOI: 10.3748/wjg.v20.i26.8691
|View full text |Cite
|
Sign up to set email alerts
|

Drain amylase value as an early predictor of pancreatic fistula after cephalic duodenopancreatectomy

Abstract: DFA1 ≥ 1200 U/L is an important predictive factor for PF of any degree. The trend of DFA3 (decrease of < 50%) compared to DFA1 is a significant factor in the differentiation of CRPF from transient BPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The placement of surgical drain tubes allows early detection of pancreatic leak by measuring post-operative drain tube fluid amylase. 12,13 In addition, it may serve to establish a controlled pancreatico-cutaneous fistula to minimize the degree of sepsis if pancreatic leak is present. However, drain tube placement carries potential infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of surgical drain tubes allows early detection of pancreatic leak by measuring post-operative drain tube fluid amylase. 12,13 In addition, it may serve to establish a controlled pancreatico-cutaneous fistula to minimize the degree of sepsis if pancreatic leak is present. However, drain tube placement carries potential infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Early prediction of the likely non‐occurrence of a POPF would be clinically useful, allowing a patient to be placed safely on a fast‐track postoperative protocol. Several preoperative, intraoperative and postoperative risk factors have been analysed previously and found to be associated with POPF.…”
Section: Introductionmentioning
confidence: 99%
“…4,7,[17][18][19][20][21][22][23][24][25][26][27][28][29] The process of selecting trials for inclusion is shown in Figure 1. The characteristics of these 15 studies are shown in Table 1.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The Fagan plot in DPA1 for overall POPF [17][18][19][20][21][22][24][25][26][27][28][29] calculated that the positive post-test probabilities (post-test (þ)) were 0.57, 0.80, 0.92 respectively, and the negative posttest probabilities (post-test (À)) were 0.04, 0.10, 0.25 respectively when the pretest probability was 25% or 50% or 75%. For PPA1 [22,[27][28][29], the post-tests (þ) were 0.39, 0.66, 0.85 respectively, and the post-tests (À) were 0.12, 0.30, 0.56 respectively.…”
Section: Fagan Plot Analysismentioning
confidence: 99%
See 1 more Smart Citation